Conceptions of Self and Performance-Related Feedback in the U.S., Japan and China - Bailey, James R.; Chen, Chao C.; Dou, Sheng-Gong (Journal of International Business Studies, 1997)
Effective international management requires knowledge of culturally patterned self-concepts and concomitant feedback desires. This paper argues that the cultural forces of individualism versus collectivism shape the self-concept, and by extension individual performance evaluation and feedback seeking. We present a comparative study to test the hypotheses that U.S. respondents desire success feedback (whereas Japanese and Chinese desire feedback), show more initiative and perceive more direct workplace feedback than do either Japanese or Chinese respondents. Strong support was found for comparisons between the U.S. and Japan, but the Chinese consistently departed from predictions. We interpret these results in terms of recent reforms in the People's Republic of China, and discuss implications of the study for international management.